2018
DOI: 10.1186/s12893-018-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraoperative handling and wound healing between (NEOSORB® plus) and coated polyglactin 910 suture (NEOSORB®): a prospective, single-blind, randomized controlled trial

Abstract: BackgroundCoated polyglactin 910 suture with chlorhexidine (NEOSORB® Plus) has recently been developed to imbue the parent suture with antibacterial activity against organisms that commonly cause surgical site infections (SSI). This prospective, single-blinded, randomized trial, was performed to compare the intraoperative handling and wound healing characteristics of NEOSORB® Plus with those of the traditional polyglactin 910 suture (NEOSORB®) in urologic surgery patients.MethodsPatients (aged 19 to 80 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Early studies showed a reduction of the number of bacteria in vitro and wound infections in animals using triclosan-coated sutures, and this effect was subsequently confirmed in clinical studies [28,29]. Several novel antimicrobial coatings are now available, but still, no clinical studies have been done that compare the efficacy with non-coated sutures [30].…”
Section: Resultsmentioning
confidence: 95%
“…Early studies showed a reduction of the number of bacteria in vitro and wound infections in animals using triclosan-coated sutures, and this effect was subsequently confirmed in clinical studies [28,29]. Several novel antimicrobial coatings are now available, but still, no clinical studies have been done that compare the efficacy with non-coated sutures [30].…”
Section: Resultsmentioning
confidence: 95%